Knowledge and Use of PEP and PrEP Among Key Populations Tested in Community Centers in Portugal - Simões, Daniel; Meireles, Paula; Rocha, Miguel; Freitas, Rosa; Aguiar, Ana; Barros, Henrique (Frontiers in Public Health, 2021)
Background: Pre-Exposure Prophylaxis (PrEP) and Post-Exposure Prophylaxis (PEP) have been increasingly available in Europe. Due to the high burden of HIV in key populations, these could benefit from their use. In 2016 in Portugal, an open, non-interval, prospective cohort study was established in a network of 26 community-based voluntary counselling and testing centers. Data collected included questions on PEP and PrEP knowledge and use. We estimated the proportion of PEP and PrEP knowledge and its use among key populations visiting the centers between 2016 and 2019. Method and results Individuals who self-identify as at least one key population for HIV: men who have sex with men (MSM), people who inject drugs (PWID), sex workers (SW), migrants, and male-to-female transgender individuals (MTF), responded to questions regarding PEP and PrEP knowledge and use while waiting for their test results, between 2016 and 2019 (n=12,893 for PEP; n=10,973 for PrEP). Reported knowledge was low in all key populations for both tools: 15.7% of respondents reported knowing of PEP and 10.9% PrEP over the course of the four years. PEP was used by 231 (1,8%) and PrEP by 45 (0,4%) respondents, MSM being 40 of the 45 PrEP users and 122 of the 231 PEP users. Multivariate logistic regression showed multiple factors associated with knowledge of the tools including age, education, country of birth, gender, year of test, reactive HIV test in the same visit, reporting an STI or condomless sex in the last 12 months, and being MSM, SW, or both. Conclusions: Knowledge and use of PEP and PrEP remain low among key populations in Portugal, although MSM and MTF present better indicators. The need remains to increase knowledge and use among those at risk for HIV infection.